Application of System Dynamics in the Forecasting Water Resources Demand in Tianjin Polytechnic University - Zhai, Chunjian; Zhang, Hongwei; Zhang, Xuehua (2009 International Conference on Artificial Intelligence and Computational Intelligence, 2009)
Accurate prediction of water resources demand plays an important role in the system which integrates water resources management promotes and balance efficiency and allocation of water demand. This article introduces the ITHINK software for the forecasting water resources demand. System Dynamics is a brand-new subject on the basis of operation research, system theory, cybernetics, information feedback theory, decision theory and computer science. The model which is proposed in this article is dominated by three stocks, five flows and thirty-one converters. As regards Tianjin polytechnic university, the model is developed for predicting the tendency of the planning years, based on analysis of water resources. The practical verification showed this method forecast relative error was lower than 5%. Thus the predicting outcome showed that System dynamics forecasting result can offer accurate quantitative information to water resources management system. And that proved that System Dynamics method was an available tool for resources plan.